The Ebb and Flow of the Relationship Between Islamic Boarding Schools and Rulers: A Comparative Study of Turkish Madrasahs and Traditional (Salaf) Islamic Boarding Schools in Indonesia - Muhammad Aga Yudha; Nabil Yasar Rudi; Rakha Abinaya (Penerbit Hellow Pustaka, 2025)
Traditional Islamic religious educational institutions, such as Islamic boarding schools, are one of the oldest educational institutions that have inspired the birth of various modern secular educational institutions in Muslim countries. However, over time, traditional Islamic boarding schools have been faced with a difficult choice, namely whether they should adapt to modernity or maintain their existence independently and separately from the outside world. This situation does not have a major impact on most Islamic boarding schools, because Islamic boarding schools are based in rural communities. On the other hand, the exclusive attitude of Islamic boarding schools also results in minimal political support to protect the interests of Islamic boarding schools so that they continue to exist. The relationship between Islamic boarding schools and political authorities often experiences ups and downs that sometimes harm Islamic boarding schools, even causing the closure of Islamic boarding schools. This article discusses the comparison of traditional Islamic boarding school education in Turkey and Indonesia and the ups and downs of the relationship between Islamic boarding schools and the ruling authorities in Turkey in the early days of the Republic and Salaf Islamic boarding schools in Indonesia during the New Order. There are several academic reasons underlying the importance of this theme. First, Islamic boarding schools in Turkey and Indonesia face similar challenges, namely a situation where political authorities do not recognize Islamic boarding schools as official educational institutions protected by the state. Second, both are managed independently and independently. Third, Islamic boarding schools in both countries are based on national nationalism and have the same scientific genealogical roots. This study uses a literature study method by relying on books, articles, and relevant books as references.